Students’ Actional Competence in Presentation Skills in EFL Classroom: A Lesson of Communicative Language Teaching Implementation - Afifah, Elvira; Pratiwi, Dwiyani; Gharamah, Fadhl Mohammed Awadh (Universitas Pendidikan Mandalika, 2024)
Actional competence refers to the ability to respond and understand communication processes effectively, both in oral and nonverbal communication. It involves the capacity to use language purposefully through vocabulary, words, and utterances, aligning with the 6 C’s of education, which emphasize critical skills like communication, collaboration, and creativity. This study investigates the actional competence demonstrated by students in presentation skills within an EFL classroom. Using a qualitative approach, specifically a case study design, the research aimed to identify the extent to which students applied actional competence during their presentations. The study was conducted with 18 students from a private school in Yogyakarta, which was in the process of transitioning from the 2013 curriculum (K13) to the new Merdeka curriculum. The data collection instruments included observation checklists, interview guidelines, and audio recordings to capture and analyze students’ presentations. The research identified seven key models of actional competence used by the students during their presentations. These models include Information Exchange, Interpersonal Exchange, Expressing Opinion, Expressing Feeling, Suasion, Problem-solving, and Future Scenario. The findings suggest that Information Exchange was the most frequently used competence, indicating that students were highly focused on providing and receiving information during their presentations. The conclusion shows that the actional competence is a critical component of successful presentation skills, especially in an academic context. The study recommends that students and presenters be encouraged to actively develop and apply actional competence in communicative language practices to enhance their performance and overcome challenges in EFL presentations. This approach can lead to more effective and engaging presentations, promoting better learning outcomes in the classroom.